STUDENTS’ PERSPECTIVES OF QUALITY EDUCATION AT A SELECTED SOUTH AFRICAN UNIVERSITY - Unathi Juliet Nkalane,; Bulelwa Makena,; Ntando Elliot Mpahla, (International Journal of Innovative Technologies in Social Science, 2024)
This study aimed to investigate the perspectives of undergraduate students in the TME (Technology and Mathematics Education) department within the Faculty of Education at a South African higher education institution regarding the quality of education they receive. Quality education is vital for equipping students with the knowledge and skills necessary for their academic and professional growth. The research was framed by the Octet of Quality Theoretical Framework in Higher Education developed by Zaki and Rashidi. A qualitative case study approach was employed on ten Technology and Mathematics Education (TME) students to gather rich and in-depth data that would offer profound insights into the experiences of the students. Data collection was carried out through semi-structured interviews, and the interview responses were subjected to thematic content analysis. The primary findings of the study revealed several challenges, including limited access to resources as well as student support and involvement in curriculum. These challenges can hinder the attainment of quality education. In conclusion, it is evident that both students and academics require support to ensure the delivery of quality education. To bridge the gap in achieving quality education, this paper suggests that students' perspectives on quality education are multifaceted and necessitate focused attention from higher education institutions. By addressing these multifaceted concerns, institutions can take substantial steps toward enhancing the overall quality of education for their students.